2004
DOI: 10.1007/s00134-004-2282-9
|View full text |Cite
|
Sign up to set email alerts
|

Combined skin disinfection with chlorhexidine/propanol and aqueous povidone-iodine reduces bacterial colonisation of central venous catheters

Abstract: Skin disinfection with propanol/chlorhexidine followed by PVP-iodine was superior in the prevention of microbial CVC colonisation compared to either of the regimens alone. These results support the concept that catheter infections can originate from bacterial translocation at the time of catheter insertion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
3
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 27 publications
0
43
3
3
Order By: Relevance
“…17 The approach is also supported by a number of studies that have demonstrated better decontamination rates of skin microorganisms at the incision site with double-agent skin preparation. 13,[18][19][20][21] We accept that this is a retrospective analysis, and may therefore be biased by incomplete case acertainment due the skin preparation type having not been recorded for all surveillance cases. We do, however, have robust prospective identification of all patients, a robust definition of SSI and the prospective follow-up of patients to record the occurrence of an SSI, which allows for a meaningful interpretation of our data.…”
Section: Discussionmentioning
confidence: 99%
“…17 The approach is also supported by a number of studies that have demonstrated better decontamination rates of skin microorganisms at the incision site with double-agent skin preparation. 13,[18][19][20][21] We accept that this is a retrospective analysis, and may therefore be biased by incomplete case acertainment due the skin preparation type having not been recorded for all surveillance cases. We do, however, have robust prospective identification of all patients, a robust definition of SSI and the prospective follow-up of patients to record the occurrence of an SSI, which allows for a meaningful interpretation of our data.…”
Section: Discussionmentioning
confidence: 99%
“…[9,10] 2) Cleaning the skin with alcoholic chlorhexidine 0.5%. [11,12] 3) Using a checklist during catheter insertion to ensure adherence to infection-control practices. 4) Using the subclavian vein as the preferred insertion site and avoiding the femoral vein if possible And 5) Daily evaluation to determine whether catheters were unnecessary and could be removed [13,14,15,16,17,18].…”
Section: Methodsmentioning
confidence: 99%
“…Many antimicrobial agents exhibit restricted permeation of the skin (8) and fail to reach the deeper layers, including the hair follicles, which harbor coagulasenegative staphylococci (2,7,8,13,15) and propionibacteria (13). Commensal microorganisms may therefore persist at the site of incision following skin antisepsis (4, 22), and such resident organisms may cause infection when the protective skin barrier is breached during surgical procedures (12,20,26). Therefore, effective and rapid permeation of the applied antiseptic agent into the deeper layers of the skin is essential in preventing infections associated with invasive procedures.…”
mentioning
confidence: 99%